Satisfied with the worst health outcomes or unsatisfied with the best: explaining the divergence between good patient-reported outcomes and low satisfaction and vice versa among knee arthroplasty patients – a retrospective cohort study - Lukas Schöner; Viktoria Steinbeck; Reinhard Busse; Carlos J. Marques (Journal of Orthopaedic Surgery and Research)
Abstract Objectives Total knee arthroplasty (TKA) is an effective treatment for patients with end-stage knee osteoarthritis but some patients exhibit a discrepancy between patient-reported outcomes (PROs) and patient satisfaction (PS). This study aims to identify predictors for patients reporting unfavorable PROs but high PS and vice versa. Materials and methods This retrospective cohort study categorized patients from nine German hospitals into four groups based on (i) whether they achieved a minimal clinically important difference (MCID) in knee functionality, measured with a joint-specific PRO from admission to 12-month post-surgery; and (ii) whether they were satisfied at 12 months post-surgery. The groups were (A) Satisfied Achievers (satisfied, MCID reached), (B) Dissatisfied Achievers (not satisfied, MCID reached), (C) Satisfied Non-Achievers (satisfied, MCID not reached) and (D) Dissatisfied Non-Achievers (not satisfied, MCID not reached). Exploratory analyses were performed to understand differences between the four groups using chi-squared tests and ANOVA. Multinomial logistic regression models were conducted to identify predictors for the allocation of patients in groups. Results A total of 1546 knee arthroplasty patients with a mean age of 65.9 years, 54.1% female, were included. 1146 (74.1%) patients were Satisfied Achievers, 131 (8.5%) were Dissatisfied Achievers, 141 (9.1%) were Satisfied Non-Achievers, and 128 (8.3%) Dissatisfied Non-Achievers. The results showed that higher improvements in health-related quality of life, pain and fatigue symptoms significantly decreased the likelihood of being a Dissatisfied Achiever and a Satisfied Non-Achiever. Comorbidities of blood circulation, chronic back pain or diabetes increased the likelihood of being a Dissatisfied Achiever, while depression decreased the likelihood of being a Satisfied Non-Achiever. Conclusion Addressing individual health concerns, e.g. through expectation management, and assessing alternative treatment options might improve satisfaction in line with functional improvements. A closer evaluation at which physical impairment level surgery is beneficial could help to improve the care of Satisfied Non-Achievers.